Longitudinal MRI study after carbon ion and photon irradiation: shorter latency time for myelopathy is not associated with differential morphological changes - Welzel, Thomas; Bendinger, Alina L.; Glowa, Christin; Babushkina, Inna; Jugold, Manfred; Peschke, Peter; Debus, Jürgen; Karger, Christian; Saager, Maria (Radiation oncology, 2021)
Background:  Radiation-induced myelopathy is a severe and irreversible complication that occurs after a long symptom-free latency time if the spinal cord was exposed to a significant irradiation dose during tumor treatment. As carbon ions are increasingly investigated for tumor treatment in clinical trials, their effect on normal tissue needs further investigation to assure safety of patient treatments. Magnetic resonance imaging (MRI)-visible morphological alterations could serve as predictive markers for medicinal interventions to avoid severe side effects. Thus, MRI-visible morphological alterations in the rat spinal cord after high dose photon and carbon ion irradiation and their latency times were investigated. - Methods:  Rats whose spinal cords were irradiated with iso-effective high photon (n = 8) or carbon ion (n = 8) doses as well as sham-treated control animals (n = 6) underwent frequent MRI measurements until they developed radiation-induced myelopathy (paresis II). MR images were analyzed for morphological alterations and animals were regularly tested for neurological deficits. In addition, histological analysis was performed of animals suffering from paresis II compared to controls. - Results:  For both beam modalities, first morphological alterations occurred outside the spinal cord (bone marrow conversion, contrast agent accumulation in the musculature ventral and dorsal to the spinal cord) followed by morphological alterations inside the spinal cord (edema, syrinx, contrast agent accumulation) and eventually neurological alterations (paresis I and II). Latency times were significantly shorter after carbon ions as compared to photon irradiation. - Conclusions:  Irradiation of the rat spinal cord with photon or carbon ion doses that lead to 100% myelopathy induced a comparable fixed sequence of MRI-visible morphological alterations and neurological distortions. However, at least in the animal model used in this study, the observed MRI-visible morphological alterations in the spinal cord are not suited as predictive markers to identify animals that will develop myelopathy as the time between MRI-visible alterations and the occurrence of myelopathy is too short to intervene with protective or mitigative drugs.